2017
DOI: 10.1007/s00128-017-2201-8
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Induction as Indicator of Low Level Metal Exposure to Aquatic Macroinvertebrates from a Relatively Unimpacted River System in South Africa

Abstract: The Marico River is relatively unaffected by anthropogenic activities. However, metal concentrations-mainly from natural sources-occasionally exceed environmental quality guidelines. Macroinvertebrates are capable to react to these metals through processes such as the induction of metallothioneins (MTs). The aims of this study were to determine whether the induction of MTs can be used as indicator of natural metal exposure in not anthropogenically impacted systems and whether there are relationships between me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Heavy metal pollution by anthropogenic activities is a major concern due to its impact on the environment and aquatic organisms [ 101 , 102 ]. Anthropogenic sources of metals include wastewater, traffic emissions, coal and oil combustion, industrial production, and many others [ 103 ]. Aquatic organisms counteract continuously with heavy metal ions also ingesting them from their diet, and their removal from tissues is not always constant as several factors come into play, such as time of exposure to the metal, temperature, metabolic activity, and metal chemistry.…”
Section: An Overview Of Emerging Contaminants Toxicitymentioning
confidence: 99%
“…Heavy metal pollution by anthropogenic activities is a major concern due to its impact on the environment and aquatic organisms [ 101 , 102 ]. Anthropogenic sources of metals include wastewater, traffic emissions, coal and oil combustion, industrial production, and many others [ 103 ]. Aquatic organisms counteract continuously with heavy metal ions also ingesting them from their diet, and their removal from tissues is not always constant as several factors come into play, such as time of exposure to the metal, temperature, metabolic activity, and metal chemistry.…”
Section: An Overview Of Emerging Contaminants Toxicitymentioning
confidence: 99%
“…Benthic macroinvertebrates have been identified as useful bioindicators of REE contamination. Given that the dominant macroinvertebrate in these streams, Zapada haysii , is common at ARD streams throughout the Colorado Rocky Mountains, this species is likely to be tolerant of low pH, trace metals and REEs. Even so, the Zn content in the macroinvertebrate biomass at the ARD impacted sites was in the range of that observed in macroinvertebrates exposed to low level metal contamination . The Zn content was also generally much higher than the REE content, as well as the Pb and Cd content.…”
Section: Resultsmentioning
confidence: 69%
“…Although the biological mechanisms for tolerance to REEs are not well-known, potential mechanisms are surface adsorption of the carapace of macroinvertebrates and sequestering of REEs in metallothionein proteins . In this context, for the headwater streams where natural ARD has been occurring for millennia, the potential impact of increasing REE concentrations may be limited for lower trophic levels.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the surface area of the lumen in the tissue are a mechanism to deal with the presence of large amounts of heavy metals and how to get rid of them through the process of cell decay (Morgan et al 2002). Heavy metal detoxification was performed by synthesizing MT as a form of self-defense and maintaining body homeostasis (Kemp et al 2017). Hertika et al (2018) reported a positive correlation among the levels of MT with metals Pb, Cd and Hg.…”
Section: Mt Levels In Cheumatopsyche Spmentioning
confidence: 99%